Catch That Cat! - Viswanath, Tharini; Illustrations by Raj, Nancy (Karachi Oxford University Press, 2016)
When her friend$1 (Bs cat, Kaapi, gets lost, Dip Dip goes off to look for it $1 (Bon the road, inside dustbins, behind houses, under bushes, everywhere. And when Kaapi finally climbs up a tree and can$1 (Bt come down, the only thing to do is$1! =(B? Nancy$1 (Bs exuberant illustrations delightfully capture the spirited little girl for whom being on a wheelchair stops her from nothing!s
Include Illustrations.
Fiction for Children.
Keywords: Cats -- Children with disabilities -- Children's stories, Indic (English)